2014
DOI: 10.1111/jocd.12073
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of various growth factors and cytokines on type I collagen and hyaluronan production in human dermal fibroblasts

Abstract: Various growth factors and cytokines on the regulation of type I collagen and hyaluronan in human dermal skin probably function as key factors in skin remodeling and skin aging. Our profile may help to apply to cosmeceutical area maintaining as young skin through the increase in extracellular matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 31 publications
5
41
1
Order By: Relevance
“…H,I). These findings are in agreement with reports showing stimulation of collagen production in vitro by rhIL-15 (Kim et al ., 2014) and PPAR agonists (Ham et al ., 2010) and demonstrate that physiologic elevations of circulating IL-15 can mimic some of beneficial effects of exercise training on aging skin and skeletal muscle metabolism. Furthermore, as inflammation is a hallmark of aging and metabolic dysfunction (Green et al ., 2011), we measured plasma cytokines from each treatment group and found that rmIL-15 and exercise treatment reduced circulating levels of the inflammatory cytokines IL-6 and MCP-1 (Fig6J,K).…”
Section: Resultsmentioning
confidence: 99%
“…H,I). These findings are in agreement with reports showing stimulation of collagen production in vitro by rhIL-15 (Kim et al ., 2014) and PPAR agonists (Ham et al ., 2010) and demonstrate that physiologic elevations of circulating IL-15 can mimic some of beneficial effects of exercise training on aging skin and skeletal muscle metabolism. Furthermore, as inflammation is a hallmark of aging and metabolic dysfunction (Green et al ., 2011), we measured plasma cytokines from each treatment group and found that rmIL-15 and exercise treatment reduced circulating levels of the inflammatory cytokines IL-6 and MCP-1 (Fig6J,K).…”
Section: Resultsmentioning
confidence: 99%
“…PDGF induces dermal fibroblasts to produce collagen during wound healing[110]. PDGF incorporated into skin scaffolds improve wound healing due to increased collagen deposition[111].…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
“…Besides the participation of MCP-1 in early inflammation, additional functions during the process of wound healing are discussed, there under the influence of MCP-1 on extracellular matrix degradation by matrix metalloproteinases, which is also an important step during the process of angiogenesis within the healing sequence [24]. Not only matrix degradation, but also the synthesis of collagens and hyaluronan by fibroblasts seems to be triggered by MCP-1 during skin remodelling [24,25]. We also focused on MCP-1 in this study because there is a strong link of MCP-1 over-expression and fibrosis development in different organs [26], an aspect with high relevance for soft tissue repair [11].…”
Section: Introductionmentioning
confidence: 99%